Empowering sex workers? Critical reflections on peer-led risk-reduction workshops in Soweto, South Africa - Susann Huschke (Taylor & Francis Group, 2019)
Background: Sex workers in South Africa face various forms of structural and interpersonal violence, including police violence, exclusion from health services, and stigmatization and marginalization within their communities. In an attempt to counteract the harmful health effects of criminalization and exclusion, risk-reduction workshops are a key component of HIV prevention programs globally. This paper offers a critical investigation of Creative Space workshops - a South African model of risk-reduction workshops for sex workers - taking place in Soweto, Johannesburg. Drawing on Paulo Freire's work, the paper explores the potential of these workshops to contribute to the empowerment, health and well-being of sex workers. Objectives: The aim of this paper is to investigate the social and psychological effects of peer-led risk-reduction workshops for sex workers in Soweto, South Africa, with a particular focus on the ways in which they might contribute to community empowerment. Methods: This paper is based on in-depth interviews and focus group discussions with 32 sex workers conducted as part of a 20-month ethnographic study (December 2015 to July 2017). Data was analyzed combining inductive thematic analysis with a theoretical frame based on Freire's theory of community empowerment. Results: Peer-led risk-reduction workshops can serve as a 'safe space' for sex workers and distribute empowering forms of knowledge, particularly regarding health issues and rights. However, divisions between different groups of sex workers and between sex workers and non-sex workers counteract the potential benefits of the workshops. Conclusions: Peer-led sex worker programs are likely to be more empowering when they are committed to raising critical consciousness and creating solidarity, and embedded in community action, focusing on common issues such as institutionalized racism, livelihood insecurity, and lack of access to safe and secure housing. Such actions would have positive outcomes on health and well-being.